Screening for Gastric and Small Intestinal Mucosal Injury with Magnetically Controlled Capsule Endoscopy in Asymptomatic Patients Taking Enteric-Coated Aspirin - Xue Chen; Feng Gao; Jie Zhang (Gastroenterology Research and Practice)
Objective. To investigate gastric and small intestinal mucosal injury in asymptomatic patients taking enteric-coated aspirin using magnetically controlled capsule endoscopy. Methods. Patients taking enteric-coated aspirin (aspirin group) and healthy controls (control group) were recruited from Beijing Anzhen Hospital, Capital Medical University, between September 2017 and May 2018, and undertook magnetically controlled capsule endoscopy. Results. Twenty-six subjects were recruited to the aspirin group and twenty-six to the control group; the median Gastrointestinal Symptom Rating Scale scores were 3.50 and 3.00 (P=0.200), the median gastric Lanza scores were 2.50 and 1.00 (P<0.001), the small intestinal Lanza scores were 1.00 and 0.00 (P<0.001), the gastric controlled examination times were 50.0 and 51.0 min (P=0.171), the small intestinal transit times were 240.0 and 238.0 min (P=0.654), and the capsule excretion times were 24.0 and 24.0 hours (P=0.956), respectively. Conclusions. Rates of gastric and small intestinal mucosal injuries were significantly higher in patients without obvious gastrointestinal symptoms taking enteric-coated aspirin compared to healthy controls. Magnetically controlled capsule endoscopy constitutes a safe, real-time screening modality for gastric and small intestinal mucosal injury in patients taking enteric-coated aspirin.